2015
DOI: 10.1179/1743278215y.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pH2S influence on 3% Cr tubing steel corrosion behaviours in CO2–H2S–Clenvironment

Abstract: A series of experiments were conducted in autoclave to investigate corrosion properties of low Cr oil country tubular goods in CO 2 /H 2 S saturated brine solution (3 wt-%NaCl) at 90uC. Test material is 3Cr-80, which is gradually accepted in oil and gas industry, especially for downhole tubing and casing. The CO 2 partial pressure was fixed at 4?0 bar in all experiments, and the H 2 S partial pressure was varied from 0, 2, 4, 8, 20, 40 and 800 mbar to 4000 mbar (4 bar). The results show that when the pH 2 S va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Once the concentrations of [Fe 2+ ] × [S 2− ] and [Fe 2+ ] × [CO 3 2− ] exceed the solubility of FeS and FeCO 3 , FeS and FeCO 3 crystals will deposit on the metal surface (Equations and ) . As H 2 S/CO 2 acid gas is introduced into the autoclave, the solution in the autoclave is acidic . FeCO 3 crystals are prone to decompose in the acidic environment, while FeS is stable in this environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the concentrations of [Fe 2+ ] × [S 2− ] and [Fe 2+ ] × [CO 3 2− ] exceed the solubility of FeS and FeCO 3 , FeS and FeCO 3 crystals will deposit on the metal surface (Equations and ) . As H 2 S/CO 2 acid gas is introduced into the autoclave, the solution in the autoclave is acidic . FeCO 3 crystals are prone to decompose in the acidic environment, while FeS is stable in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…[22] As H 2 S/CO 2 acid gas is introduced into the autoclave, the solution in the autoclave is acidic. [23,24] FeCO 3 crystals are prone to decompose in the acidic environment, while FeS is stable in this environment. Besides this, the solubility product K spFes of FeS is lower than that of K spFeCO3 (25°C, K spFes = 6.3 × 10 −18 , K spFeCO3 = 3.2 × 10 −11 ), and more FeS are deposited on the metal surface.…”
Section: Discussionmentioning
confidence: 99%
“…According to the survey, scholars across the world have made great achievement in the corrosion of CO 2 and H 2 S. It was found that the CO 2 /H 2 S corrosion was mainly affected by gas partial pressure, temperature, pH, fluid flow rates, medium, material and other factors (Yan et al , 2015; Zhang et al , 2015). However, the application research of sulfur-resistant steel at 350°C has not been found.…”
Section: Introductionmentioning
confidence: 99%
“…However, a small amount of H 2 S may be produced by sulfate-reducing bacteria [13]. The brine solution, containing CO 2 and H 2 S, is a corrosive medium, which accelerated localised corrosion such as pitting corrosion and sulphide stress corrosion cracking [12][13][14][15][16][17][18][19][20][21]. To date, a couple of studies have been conducted with a focus on the role of trace H 2 S in corrosion of carbon steel in the CO 2 -saturated solution [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%